Return to Work Following Intramedullary Nailing of Lower-Limb Long-Bone Fractures in South Africa. (5th April 2023) - Masterson, Samuel; Laubscher, Maritz; Maqungo, Sithombo; Ferreira, Nando; Held, Michael; Harrison, William J.; Graham, Simon Matthew
Abstract : Background: Injuries are one of the leading causes of global death and disability and commonly have substantial economic implications. The economic impact of injuries is particularly pronounced in low- and middle-income countries, where 90% of injuries occur. In this study, we aimed to assess return-to-work rates of individuals who sustained a lower-limb long-bone fracture in South Africa and to identify factors that influence the ability to return to employment. Methods: This prospective cohort study was conducted across 2 tertiary trauma centers in Cape Town, South Africa. Adults who received intramedullary nail fixation for a lower-limb fracture between September 2017 and December 2018 were recruited and followed for 18 months postoperatively. The participants' return to employment was assessed at 6 and 18 months post-injury. Multivariate logistic regression was used to identify factors that influence post-injury employment. Results: Of the 194 participants enrolled, 192 completed follow-up. The study population had a median age of 33.0 years, and most of the participants (76.6%) were male. Seventy-five percent of the participants were employed before their injury. At 6 and 18 months post-injury, 34.4% and 56.3% of participants, respectively, were employed. Of those employed pre-injury, 70.1% had returned to work at 18 months. Multivariate regression identified increasing age, unemployment prior to injury, and working in the informal employment sector as factors that impede an individual's likelihood of working 18 months post-injury. For those in employment prior to injury, increasing age was the only factor found to impede the likelihood of returning to work following an injury. Conclusions: This study highlights the profound effect that lower-limb long-bone fractures may have on an individual's ability to return to work in South Africa, with the potential to cause substantial economic impact on an individual's livelihood and that of their dependents. Level of Evidence: Prognostic Level III . See Instructions for Authors for a complete description of levels of evidence.